Concomitant presentation of hydatid cyst of kidney and liver - A rare case report - Vadamalai, Kopperundevi (Indian Journal of Case Reports, 2016)
Hydatid cyst, a zoonotic disease, caused by larval stage of Echinococcus granulosus occurs worldwide. The most common sites of involvement by hydatid cyst are liver followed by lung. Kidney involvement in hydatid cyst is very rare accounting for only 2 – 3% in endemic areas. We report a case of 57 year old male who presented with right upper abdominal lump and diagnosed as a case of hydatid cyst of both kidney and liver. He underwent right nephrouretrectomy and hepatic pericystectomy. Postoperative histopathology report was consistent with hydatid cyst. This case was reported for its concomitant presentation of kidney and liver and to discuss salient radiological features and management of renal hydatid cyst.